2013
DOI: 10.1097/ccm.0b013e31828e96c0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Pain, Sedation, and Delirium in the Neurologically Critically Ill—Feasibility and Reliability of Standardized Tools

Abstract: Pain and sedation can be systematically assessed in the neurologically critically ill; the majority can also be screened for delirium features with excellent inter-rater reliability. Increased proportion of Intensive Care Delirium Screening Checklist items is associated with worse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 25 publications
1
40
0
3
Order By: Relevance
“…In the brain-injured population, although the construct validity of both scales is supported with higher scores during painful procedures (vs rest and nonpainful procedures), patients predominantly expressed pain-related behaviors that were related to level of consciousness; grimacing and muscle rigidity were less frequently observed (50,(52)(53)(54). An additional study (51), although not evaluating validity, found that BPS and BPS-NI were feasible and reliable to use in the brain-injured population. Of note, Behavioral Pain Scales have been validated in the following languages (other than French or English): CPOT-Mandarin (55), Korean (56), Spanish (57), and Swedish (58); BPS and BPS-NI-Mandarin (59).…”
Section: Behavioral Assessment Toolsmentioning
confidence: 94%
See 2 more Smart Citations
“…In the brain-injured population, although the construct validity of both scales is supported with higher scores during painful procedures (vs rest and nonpainful procedures), patients predominantly expressed pain-related behaviors that were related to level of consciousness; grimacing and muscle rigidity were less frequently observed (50,(52)(53)(54). An additional study (51), although not evaluating validity, found that BPS and BPS-NI were feasible and reliable to use in the brain-injured population. Of note, Behavioral Pain Scales have been validated in the following languages (other than French or English): CPOT-Mandarin (55), Korean (56), Spanish (57), and Swedish (58); BPS and BPS-NI-Mandarin (59).…”
Section: Behavioral Assessment Toolsmentioning
confidence: 94%
“…The BPS-NI obtained a psychometric weighted score of 14.8. Although both the BPS and the CPOT have been validated across large samples of medical, surgical, and trauma ICUs (50)(51)(52)(53)(54), studies involving brain-injured patients using the BPS (50,51) and CPOT (52)(53)(54) are small. In the brain-injured population, although the construct validity of both scales is supported with higher scores during painful procedures (vs rest and nonpainful procedures), patients predominantly expressed pain-related behaviors that were related to level of consciousness; grimacing and muscle rigidity were less frequently observed (50,(52)(53)(54).…”
Section: Behavioral Assessment Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The visual analog scale (VAS) (VAS=0, not bad at all and well tolerable;VAS=10, very painful and beyond endurance) was evaluated immediately before extubation and 30 minutes after extubation 2,23. These parameters were measured and documented by the chief nurses (Y.Y.…”
Section: Methodsmentioning
confidence: 99%
“…Along with pain and sedation, this study further demonstrates that delirium measures endorsed in the PAD guidelines can be used for systematic delirium screening among neurologically critically ill patients. 7 …”
Section: Measurementmentioning
confidence: 99%